Prognostic value of ATPase family, AAA+ domain containing 2 expression in human cancers: A systematic review and meta-analysis. Issue 39 (September 2019) - Han, Hua-Jing; Huang, Qian-Yi; Huang, Li-Jun; Chang, Fan; Diao, Qi-Zhi
Abstract: Background: ATPase family, AAA+ domain containing 2 (ATAD2) is also known as AAA+ nuclear coregulator cancer-associated protein or PRO2000. ATAD2 has been reported as a prognostic factor in different cancer types, but the association between ATAD2 high expression and survival is still unclear. Thereby, this meta-analysis was performed to evaluate the prognostic value of ATAD2 high expression in human cancers. Methods: All of the studies included were retrieved from PubMed, EMBASE, and Cochrane Library electronic databases. The clinical outcomes were evaluated by calculating hazard ratio (HR) with their 95% confidence interval (CI). Results: Thirteen studies including 2689 patients were eligible for this analysis. The pooled results showed that ATAD2 over-expression was significantly associated with shorter overall survival (OS) (HR = 2.32, 95% CI = 1.77–3.02), as well as shorter recurrence-free survival (RFS), disease-free survival (DFS), and disease-specific survival (DSS) (HR = 1.83, 95% CI = 1.51–2.23) among human cancers. Subgroup analyses for OS were implemented in terms of region, tumor type, and sample size and the results were coincident with overall pooled results. Begg funnel plot and Egger test showed the presence of publication bias for OS. Sensitivity analysis indicated that both results were not affected for removing any study. Conclusion: ATAD2 would be likely to act as a prognostic biomarker for the patients of different cancer types and provide a guide on clinical treatment. Prospective clinical studies are needed to support these findings.